VIRTUAL TEACHER - DIAGNOSIS OF THE PROBLEM - Waldemar, LIB (Trends in education, 2014)
The article constitutes an attempt to pay attention at development of modern technologies which may be applied in educational processes at every level of education and the fact that the research on possibilities and aim of their use shall be performed concurrently with them.
Keywords: education; e-education; information technologies.